Immune Checkpoints and Their Inhibition in T-Cell Lymphomas - Seňavová, Jana; Rajmonová, Anežka; Heřman, Václav; Jura, Filip; Veľasová, Adriana; Hamová, Iva; Tkachenko, Anton; Kupcová, Kristýna; Havránek, Ondřej (Folia biologica, 2024)
T-cell lymphomas (TCLs) are a rare and heterogeneous subgroup of non-Hodgkin lymphomas (NHLs), forming only 10 % of all NHL cases in Western countries. Resulting from their low incidence and heterogeneity, the current treatment outcome is generally unfavorable, with limited availability of novel therapeutic approaches. Therefore, the recent success of immune checkpoint inhibitors (ICIs) in cancer treatment motivated their clinical investigation in TCLs as well. Multiple studies showed promising results; however, cases of TCL hyperprogression following ICI treatment and secondary T-cell-derived malignancies associated with ICI treatment of other cancer types were also reported. In our review, we first briefly summarize classification of T-cell-derived malignancies, general anti-tumor immune response, immune evasion, and immune checkpoint signaling. Next, we provide an overview of immune checkpoint molecule deregulation in TCLs, summarize available studies of ICIs in TCLs, and review the above-mentioned safety concerns associa-ted with ICI treatment and T-cell-derived malignancies. Despite initial promising results, further studies are necessary to define the most suitable clinical applications and ICI therapeutic combinations with other novel treatment approaches within TCL treatment. ICIs, and their combinations, might hopefully bring the long awaited improvement for the treatment of T-cell-derived malignancies.
Keywords: pembrolizumab; OX40/OX40L; toripalimab; ALCL; sintilimab; zvířata; CTLA-4; SS; peripheral T-cell lymphoma; anaplastic large cell lymphoma; durvalumab; anti-PD-1; ENKTL; immune checkpoint inhibitors; LAG-3; TIM-3; Immune Checkpoint Inhibitors; nivolumab; Animals; Lymphoma, T-Cell; TIGIT; anti-PD-L1; inhibitory kontrolních bodů; PD-L1; avelumab; proteiny kontrolních bodů imunitní reakce; mycosis fungoides; ipilimumab; Immune Checkpoint Proteins; geptanolimab; T-cell lymphoma; T-cell-derived malignancies; MF; PD-1; anti-CTLA-4; lymfom T-buněčný; immune checkpoints; lidé; Humans; PTCL; atezolizumab; extranodal NK/T-cell lymphoma; Sézary syndrome